Dampak Lingkungan Akibat Kegiatan Pariwisata di Kota Bukittinggi - Nofriya Nofriya; Ardinis Arbain; Sari Lenggogeni (Universitas Andalas, 2019)
Environmental pressure caused by tourism activities is increasing in line with the number of visitors and the development of infrastructure-related tourism to meet the needs of tourists who visit the tourist attractions. This leads to the increasing of the amount of solid and liquid waste, pollution, sanitation and aesthetic problems. Bukittinggi has a leading tourist attractions that are almost all located within the city making it easier for tourists to travel to various locations. A thorough concern on environmental sustainability has not been undertaken by the tourism sector of Bukittinggi City. Bukittinggi is currently overshadowed by the concerns of the carrying capacity of the city to accommodate several functions simultaneously within a limited area. The purpose of this research is to analyze the environmental problems caused by tourism activities in Bukittinggi City. This research was conducted by qualitative approach using in-depth interview to sector related with tourism, observation and literature study. Research activities conducted in June to October 2017. The results showed that tourism activities that tend to be centralized in the city center resulted in congestion and lack of parking space. The increase in tourists is followed by increased waste generation, energy use, CO2 emissions and water consumption. It is suggested to the government to synergize the policy of tourism development with the concept of sustainable development. Keywords: Sustainable Tourism , Tourism Environmental Impact, Ecotourism, Sustainable Development ABSTRAK Tekanan lingkungan yang disebabkan oleh kegiatan pariwisata semakin meningkat seiring dengan jumlah pengunjung dan pengembangan infrastruktur untuk memenuhi kebutuhan wisatawan. Hal ini menyebabkan meningkatnya jumlah limbah padat dan cair, polusi, sanitasi dan masalah estetika. Kota Bukittinggi memiliki tempat-tempat wisata yang terkenal dan hampir semuanya terletak di dalam kota sehingga memudahkan wisatawan untuk melakukan perjalanan ke berbagai lokasi. Akan tetapi, perhatian menyeluruh terhadap kelestarian lingkungan belum dilakukan oleh sektor pariwisata. Sedangkan Kota Bukittinggi saat ini dibayangi oleh kekhawatiran daya dukung kota untuk mengakomodasi beberapa fungsi secara bersamaan dalam area terbatas. Tujuan dari penelitian ini adalah untuk menganalisis masalah lingkungan yang disebabkan oleh kegiatan pariwisata di Kota Bukittinggi. Penelitian ini dilakukan dengan pendekatan kualitatif menggunakan wawancara mendalam pada sektor yang terkait dengan pariwisata, observasi dan studi literatur. Kegiatan penelitian dilakukan pada bulan Juni hingga Oktober 2017. Hasil penelitian menunjukkan bahwa kegiatan pariwisata yang cenderung terpusat di pusat kota mengakibatkan kemacetan dan kurangnya tempat parkir. Peningkatan wisatawan diikuti oleh peningkatan timbulan sampah, penggunaan energi, emisi CO2 dan konsumsi air. Disarankan kepada pemerintah untuk mensinergikan kebijakan pengembangan pariwisata dengan konsep pembangunan berkelanjutan.Kata kunci: Pariwisata berkelanjutan, Dampak lingkungan pariwisata, Pembangunan berkelanjutan